Influence of antimony substitution on spontaneous strain and thermodynamic stability of lanthanum orthoniobate. Issue 2 (March 2015) - Mielewczyk-Gryn, A.; Wachowski, S.; Lilova, K.I.; Guo, X.; Gazda, M.; Navrotsky, A.
Abstract: Analysis of the influence of antimony substitution on the temperature dependence of unit cell distortion in lanthanum orthoniobate has been performed. The values of spontaneous strain and Landau order parameter for three different antimony contents have been calculated. The monoclinic–tetragonal phase transition occurring for antimony substituted lanthanum orthoniobate was found to be of the second order. High temperature oxide melt solution calorimetry has shown that antimony substitution has little influence on the stability of the monoclinic phase. The average value of enthalpy of formation of antimony substituted lanthanum orthoniobate with fergusonite structure is −132.0±0.8 kJ/mol, and that of scheelite structure is −126.4±1.5 kJ/mol, implying greater stability for the former polymorph.